المشكلات التي تواجه طلبة كلية التمريض في جامعة تشرين - سليمان, سوسن (Latakia University Journal -Medical Sciences Series, 2018)
Student of Nursing Faculty faces during the university education a variety of problems that may affect the process of preparing him as a registered nurse able to provide professional nursing care based on a scientific basis keep up abreast technological advances in the field of health services provided to all members of society, so This descriptive study was aimed to identify the problems facing 200 students at the Faculty of Nursing at Tishreen University selected in a random stratified sample, using a questionnaire prepared for this purpose. The study found that students are facing the problem of lack of calm in the library, delayed from reaching the college, not to hear the questions of students by the teaching during the lectures, lack of presence of the supervisor during the hours of practical training, lack of cooperation between students affairs and faculty, and there were significant differences in some of those problems depending on the variable of school wear, But there were no significant differences in students' problems according to gender. The study recommended setting up appropriate plans and solutions for the problems in the study, and providing the college with teachers, halls and staff to meet the needs of the large number of students, periodic evaluation of the content of the subjects and exam questions, and the establishment of a program to allocate office hours for students. يواجه طالب كلية التمريض خلال تعلمه الجامعي مشكلات متنوعة قد تؤثر على عملية إعداده كممرض قادر على تقديم رعاية تمريضية محترفة مستنده إلى أسس علمية تواكب التقدم التكنولوجي الحاصل في مجال الخدمات الصحية المقدمة لجميع أفراد المجتمع, لذلك هدفت هذه الدراسة _الوصفية المسحية_ إلى التعرف على المشكلات التي تواجه 200 طالب في كلية التمريض في جامعة تشرين جرى اختيارهم بطريقة العينة الطبقية العشوائية, باستخدام استبيان معد مسبقاً لهذا الغرض. توصلت الدراسة إلى أن الطلاب يواجهون مشكلة عدم توفر الهدوء في المكتبة, والتأخر عن الكلية, وعدم سماع المدرس لأسئلة الطلبة أثناء المحاضرات, وقلة تواجد المشرف خلال ساعات التدريب العملي, وعدم التعاون بين شؤون الطلاب والكلية, وتوجد فروق في بعض تلك المشاكل تبعاً لمتغير السنة الدراسية, لكن لا توجد فروق في مشاكل الطلاب تبعاً لمتغير الجنس. وأوصت الدراسة بوضع الخطط والحلول المناسبة للمشكلات في الدراسة, ورفد الكلية بالمدرسين و القاعات و الموظفين لتلبية احتياجات العدد الكبير من الطلاب, والتقييم الدوري لمحتوى المواد الدراسية وأسئلة الامتحانات, ووضع برنامج تخصص فيه ساعات مكتبية للطلاب.